In Situ Detection of Trace Furfural in Aqueous Solution Based on Au Nanoparticle/Au Film Surface-Enhanced Raman Spectroscopy. (20th January 2016) - Qi, Wei; Chen, Weigen; Wan, Fu; Zou, Jingxin; Gu, Zhaoliang
Abstract : Furfural is an important chemical solvent and intermediate. Sensitive detection of this compound has attracted great interest in various fields. Surface-enhanced Raman spectroscopy (SERS) is a highly sensitive method for material detection because of its optical enhancement effect of plasmonic nanostructures. This study presents a simple and versatile method to synthesize a SERS substrate, where polyaminothiophenol (PATP) was used to realize the stable combination of Au nanoparticles (AuNPs) and Au film via self-assembly. The near-field electric field distribution was calculated using the finite difference time domain (FDTD) simulation to determine the parameters responsible for electric field enhancement. The simulation results show that SERS enhanced factors are sensitive to interparticle spacing and materials for solid support but insensitive to particle size. Moreover, the experimental results show that the optimized substrates with the highest Raman activity were formed by six layers of 60 nm AuNPs decorated on a 30 nm thick Au film, thereby validating the simulation results. The SERS factor of the optimal substrates is approximately 5.57 × 10 3, and the in situ detection limit is 4.8 ppm. The 3D Raman spectra, relative standard deviation values for major peaks, and changes in signal intensity with time show the good reproducibility and stability of the substrates.